Burden, features, and outcome of neurological involvement in acute falciparum malaria in Kenyan children. - Idro, R; Ndiritu, M; Ogutu, B; Mithwani, S; Maitland, K; Berkley, J; Crawley, J; Fegan, G; Bauni, E; Peshu, N; Marsh, K; Neville, B; et al. (2007)
CONTEXT: Plasmodium falciparum appears to have a particular propensity to involve the brain but the burden, risk factors, and full extent of neurological involvement have not been systematically described. OBJECTIVES: To determine the incidence and describe the clinical phenotypes and outcomes of neurological involvement in African children with acute falciparum malaria. DESIGN, SETTING, AND PATIENTS: A review of records of all children younger than 14 years admitted to a Kenyan district hospital with malaria from January 1992 through December 2004. Neurological involvement was defined as convulsive seizures, agitation, prostration, or impaired consciousness or coma. MAIN OUTCOME MEASURES: The incidence, pattern, and outcome of neurological involvement. RESULTS: Of 58,239 children admitted, 19,560 (33.6%) had malaria as the primary clinical diagnosis. Neurological involvement was observed in 9313 children (47.6%) and manifested as seizures (6563/17,517 [37.5%]), agitation (316/11,193 [2.8%]), prostration (3223/15,643 [20.6%]), and impaired consciousness or coma (2129/16,080 [13.2%]). In children younger than 5 years, the mean annual incidence of admissions with malaria was 2694 per 100,000 persons and the incidence of malaria with neurological involvement was 1156 per 100,000 persons. However, readmissions may have led to a 10% overestimate in incidence. Children with neurological involvement were older (median, 26 [interquartile range IQR, 15-41] vs 21 [IQR, 10-40] months; P<.001), had a shorter duration of illness (median, 2 [IQR, 1-3] vs 3 [IQR, 2-3] days; P<.001), and a higher geometric mean parasite density (42.0 [95% confidence interval CI, 40.0-44.1] vs 30.4 [95% CI, 29.0-31.8] x 10(3)/microL; P<.001). Factors independently associated with neurological involvement included past history of seizures (adjusted odds ratio [AOR], 3.50; 95% CI, 2.78-4.42), fever lasting 2 days or less (AOR, 2.02; 95% CI, 1.64-2.49), delayed capillary refill time (AOR, 3.66; 95% CI, 2.40-5.56), metabolic acidosis (AOR, 1.55; 95% CI, 1.29-1.87), and hypoglycemia (AOR, 2.11; 95% CI, 1.31-3.37). Mortality was higher in patients with neurological involvement (4.4% [95% CI, 4.2%-5.1%] vs 1.3% [95% CI, 1.1%-1.5%]; P<.001). At discharge, 159 (2.2%) of 7281 patients had neurological deficits. CONCLUSIONS: Neurological involvement is common in children in Kenya with acute falciparum malaria, and is associated with metabolic derangements, impaired perfusion, parasitemia, and increased mortality and neurological sequelae. This study suggests that falciparum malaria exposes many African children to brain insults.